(1) NonTerminationProof (EQUIVALENT transformation)
We used the non-termination processor [OPPELT08] to show that the SRS problem is infinite.
Found the self-embedding DerivationStructure:
a b b c b b c c b c c → b c c b c c b c c a b c c a b b c b b c c b c c a a a
a b b c b b c c b c c →
b c c b c c b c c a b c c a b b c b b c c b c c a a aby OverlapClosure OC 2
a b b c b b c c b c → b c c b c c b c c a b c c a b b c b b c c a b b
by OverlapClosure OC 3a b b c b b c c b c → b c c b c c b c c a b c c a b b c b b c c a a b
by OverlapClosure OC 2a b b c b b c c b c → b c c b c c b c c a b c c a b b c b b c c a a a
by OverlapClosure OC 2a b b c b b c c → b c c b c c b c c a b c c a b b c b a b
by OverlapClosure OC 3a b b c b b c c → b c c b c c b c c a b c c a b a c b a b
by OverlapClosure OC 3a b b c b b c c → b c c b c c b c c a b c c a a a c b a b
by OverlapClosure OC 3a b b c b b c c → b c c b c c b c c a a b b c c b a b
by OverlapClosure OC 3a b b c b b c c → b c c b c c b c c a a a b c c b a b
by OverlapClosure OC 3a b b c b b c c → b c c b c c a b b c b c c b a b
by OverlapClosure OC 3a b b c b b c c → b c c b c c a b b c b c c a a b
by OverlapClosure OC 2a b b c b b c c → b c c b c c a b b c b c c a a a
by OverlapClosure OC 2a b b c b b c → b c c b c c a b b c a b b
by OverlapClosure OC 3a b b c b b c → b c c b c c a b a c a b b
by OverlapClosure OC 3a b b c b b c → b c c b c c a a a c a b b
by OverlapClosure OC 3a b b c b b c → b c c a b b c c a b b
by OverlapClosure OC 2a b b c → b c c a b a
by OverlapClosure OC 3a b b c → b c c a a a
by original rule (OC 1)
a → b
by original rule (OC 1)
a b b c → b c c a b b
by OverlapClosure OC 3a b b c → b c c a a b
by OverlapClosure OC 2a b b c → b c c a a a
by original rule (OC 1)
a → b
by original rule (OC 1)
a → b
by original rule (OC 1)
a b b c → b c c a a a
by original rule (OC 1)
a → b
by original rule (OC 1)
a → b
by original rule (OC 1)
a b b c → b c c a a a
by original rule (OC 1)
a → b
by original rule (OC 1)
a → b
by original rule (OC 1)
a b b c → b c c a a a
by original rule (OC 1)
a → b
by original rule (OC 1)
a b b c → b c c a a a
by original rule (OC 1)
a → b
by original rule (OC 1)
a → b
by original rule (OC 1)
a b b c → b c c a a a
by original rule (OC 1)
a → b
by original rule (OC 1)
a → b
by original rule (OC 1)
a b b c → b c c a a a
by original rule (OC 1)